Disaster management: a study on knowledge, attitude and practice of emergency nurse and community health nurse - Ismail, Aniza; Ahayalimudin, Nurul'ain; Mohd Saiboon, Ismail (Springer, 2012)
Introduction: Disasters are unpredictable and the numbers are mounting from day to day. Disaster kills and affects people, demolishes properties and disrupts environment. In the occurrence of disaster, nurses play vital roles in dealing with the victims, therefore it is crucial for nurses to be prepared in facing disaster and its aftermath. The aim is to determine knowledge, attitude and practice of emergency nurse and community health nurse towards disaster management. Methods: This comparative cross-sectional study conducted in one of states in Malaysia. The data was collected between October and November 2011. The questionnaire distributed to randomly select 468 nurses from emergency departments and health clinics with response rate of 84.6 per cent respectively. Results: Emergency nurses and community health nurses are identified as having inadequate knowledge and practice, majority nurses of both groups portraying positive attitude and their practice are differs (p<0.001, 2=24.506). Emergency nurses who are involved in disaster response more likely to have an adequate practice (p<0.01, AOR=4.008, 95% CI=1.691 – 9.504) and those who are attended disasterrelated education/training more likely to have adequate knowledge (p<0.05, AOR=3.807, 95% CI=1.584 – 9.153) and practice (p=0.001, AOR=4.145, 95% CI=1.804 – 9.525). Attended disaster-related education/training is a predictor to the adequacy of knowledge (p<0.001, AOR=3.511, 95% CI=2.097 – 5.881) and practice (p<0.001, AOR=4.080, 95% CI=2.326 –7.156) among community health nurse likewise portraying positive attitude (p<0.05, AOR=2.042, 95% CI=1.025 – 4.069). Emergency nurses have an adequate practice as compared to community health nurse (p<0.001, AOR=2.345, 95% CI=1.474-3.730). Conclusion: It has been statistically proven that adequacy of knowledge and practice, and portraying positive attitude is driven by involvement in disaster response and attending disasterrelated education/training.